2015
DOI: 10.1590/1983-80422015233100
|View full text |Cite
|
Sign up to set email alerts
|

A teoria da moralidade comum na obra de Beauchamp e Childress

Abstract: "Principles of Biomedical Ethics" by Tom L. Beauchamp and James F. Childress, based on the concept of principlism, is the most studied book in the field of bioethics, and played a decisive role in the consolidation and global expansion of the discipline. Its four principles, however, were taken from different theories: the autonomy principle came from Kantian theory (Kant); beneficence, from utilitarian theory (Mill); justice, from the theory of justice (Rawls); and non-maleficence, from the common morality th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
(71 reference statements)
1
9
0
2
Order By: Relevance
“…An unpublished study recently carried out by Azambuja and Garrafa 32 has confirmed the pertinence of all the criticism presented so far. These authors analyzed the changes introduced in the last four editions (fourth, fifth, sixth and seventh) of the book "Principles of biomedical ethics".…”
Section: On the Other Hand Neves Emphasizes That Anglo-american Theosupporting
confidence: 60%
See 1 more Smart Citation
“…An unpublished study recently carried out by Azambuja and Garrafa 32 has confirmed the pertinence of all the criticism presented so far. These authors analyzed the changes introduced in the last four editions (fourth, fifth, sixth and seventh) of the book "Principles of biomedical ethics".…”
Section: On the Other Hand Neves Emphasizes That Anglo-american Theosupporting
confidence: 60%
“…The main criticisms formulated by two groups of bioethics scholars will be presented: first, those coming from US authors [23][24][25][26][27] and, second, from bioethicists of European and Latin American origin [28][29][30][31][32][33] . Then the central principles of international and national bioethics will be presented based on the principle of human dignity in the light of the Constitution of the Federative Republic of Brazil, national doctrine and legislation.…”
Section: Resumen Bioética: Crítica Al Principialismo Constitución Brmentioning
confidence: 99%
“…Perhaps for this reason it has been widely disseminated and articulated for the use of all ethical committees. But it is also clear that their shortcomings have raised opposition from many areas, difficult gaps to reconcile with moral theories that claim to be universal 39 . Among them are the use of prima facie principles as a starting point, which closes the door to consider that there are intrinsically immoral actions; or the reduction of medical deliberations to physical actions and external results without taking moral action into account; or the variability and ambiguity in the application of the principles, which allows someone or another to do so, provided that it is convincing 40 .…”
Section: Final Considerationsmentioning
confidence: 99%
“…And here begins the divergence, what is good, when Is it about the human being? We understand that if the basic concept of the whole moral building is not common, all moral theory will be an entelechy, something that Beauchamp and Childress reflect in successive editions 39 . The lack of unifying or at least clarifying concepts leads us to think about the need to re-conceptualize the ethical problems 54 , a comprehensive review, not only of the principles 55 , within a framework of continuous reflection 56 .…”
Section: Final Considerationsmentioning
confidence: 99%
“…The term "bioethics" was coined in English language in 1971 by the American oncologist Van Rensselaer Potter of the University of Wisconsin, in the book "Bioethics: bridge to the future." Later, André Hellegers of the Center for Bioethics of the Kennedy Institute at Georgetown University used the same term but with a strictly biomedical connotation, unlike the one used by Potter, which was more global and widespread 9 .…”
Section: Intervention Bioethicsmentioning
confidence: 99%